The Appeal of the Community Service Ads to Prevent Covid 19 #MULAIDARIKAMU - Solihin, O; Rachmadita, S A; Yasundari (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
Public service announcement are made to encourage and remind the audience about the social awareness that is being experienced in order to change an audience’s attitude, this research was conducted to determine the effect of the attractiveness of public service announcement on public attitudes in preventing Covid-19. Researchers have indicators rational attraction, emotional attraction, moral attraction, attention, understanding and acceptance. This study uses a quantitative approach with a questionnaireThe population in this study was the people of Cipadung Village, RW 14, Cibiru District, Bandung City, which amounted to 843 families. The sample was selected using cluster random sampling with a precision of 10% so that 90 samples were obtained. Data analysis used simple linear regression analysis. The results of this study indicate that there is a significant positive influence between rational attractiveness, emotional attractiveness and moral attractiveness on attitudes. As well as a significant positive effect between the attractiveness of advertising on attention, understanding and acceptance. The conclusion of this research is H0 is rejected and H1 is accepted, namely there is a significant positive effect between the Attractiveness of Public Service Announcement to prevent Covid-19 #MulaiDariKamu by Kominfo on the Attitudes of the People of Cibiru District, Bandung City on Covid-19 prevention on the Attitude of the People of Cibiru District, Bandung City on Covid Prevention-19 of 59.7% while the remaining 40.3% was due to other factors. The implication of this research is that public service announcement as an effective stimulus causes a reaction (change of attitude) from the community through the process of packaging the message.